In Vitro Activity of Ceftolozane-Tazobactam vs. Antimicrobial Non-Susceptible Pseudomonas aeruginosa Clinical Isolates Obtained from Across Canada as Part of the CANWARD Study, 2008–2016. (4th October 2017) - Walkty, Andrew; Adam, Heather J; Baxter, Melanie; Lagace-Wiens, Philippe; Karlowsky, James; Hoban, Daryl; Zhanel, George
Abstract: Background: Ceftolozane-tazobactam (C/T) is a novel β-lactam β-lactamase inhibitor combination with a broad spectrum of activity that includes Pseudomonas aeruginosa . The purpose of this study was to evaluate the in vitro activity of C/T and relevant comparators vs. a large collection of antimicrobial non-susceptible (NS) P. aeruginosa clinical isolates obtained from patients across Canada (CANWARD, 2008–2016). Methods: From January 2008 to December 2016, inclusive, 12 to 15 sentinel hospitals across Canada submitted clinical isolates from patients attending ERs, medical and surgical wards, hospital clinics, and ICUs (CANWARD). Each center was asked to annually submit clinical isolates (consecutive, one per patient/infection site) from blood, respiratory, urine, and wound infections. Susceptibility testing was performed using broth microdilution as described by CLSI. Multidrug-resistant (MDR) P. aeruginosa were defined as isolates that tested NS to at least one antimicrobial from ≥3 classes. Extensively drug-resistant (XDR) P. aeruginosa were defined as isolates that tested NS to at least one antimicrobial from ≥5 classes. Results: 3229 P. aeruginosa isolates were obtained as a part of CANWARD. The in vitro activity of C/T and relevant comparators is presented below. Conclusion: C/T demonstrated excellent in vitro activity vs. antimicrobial NS P. aeruginosa clinical isolates, including MDR, XDR, and meropenem NS subsets. It may prove useful in the treatment of infections caused by these organisms. Disclosures: D. Hoban, Abbott: Research relationship, Research support Achaogen: Research relationship, Research support Astellas: Research relationship, Research support Merck Canada: Research relationship, Research support Merck USA: Research relationship, Research support Paratek Pharma: Research relationship, Research support Pharmascience: Research relationship, Research support Sunovion: Research relationship, Research support Tetraphase: Research relationship, Research support The Medicines Co.: Research relationship, Research support Zoetis: Research relationship, Research support; G. Zhanel, Achaogen: Research relationship, Research support Astellas: Research relationship, Research support Merck Canada: Research relationship, Research support Merck USA: Research relationship, Research support Paratek Pharma: Research relationship, Research support Pharmascience: Research relationship, Research support Sunovion: Research relationship, Research support Tetraphase: Research relationship, Research support The Medicines Co.: Research relationship, Research support Zoetis: Research relationship, Research support